A Ghost’s Burial? How the Extraordinary Use of Terracottas in a Late Archaic Tomb Might Have Served to Prevent Encounters with Unhappy Spirits - Ernst-Andreas Neumann (Les Carnets de l’ACoSt)
This article is devoted to a clay tub burial from Athens, laid out in the early fifth century B.C.E., where vessels have been found in unusual types, number, and quality. Even more, central parts of the skeleton were missing. Since the objects were arranged in a very special way, the impression arises that the bones have been replaced by vessels and terracotta figurines. Discussing the reasons for such a practice, a reburial evolves as the most likely option. By a glimpse on ancient ghost stories and images, it is pointed out that the reburial might have been triggered by a certain belief: the possibility that the dead could come back to earth. It is argued that in this mindset the replacement of the corpse seemed necessary to prevent the spirit of the deceased, disturbed in his rest by the destruction of the original burial, of leaving Hades and haunting the place of the original grave.